2022
DOI: 10.1111/jomf.12898
|View full text |Cite
|
Sign up to set email alerts
|

Parent–adult child estrangement in the United States by gender, race/ethnicity, and sexuality

Abstract: Objective To provide nationally representative estimates of parent–adult child estrangement. Background Population‐level research on parent–adult child estrangement is needed to understand the full range of family dynamics in the U.S. Methods We estimate logistic regression models using data from the National Longitudinal Survey of Youth 1979 and accompanying Child and Young Adult supplement to determine estimates of estrangement (and subsequent unestrangement) from mothers (N = 8495) and fathers (N = 8119) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…By the same logic, having no contact with one child may be sufficient to aggravate the impact of divorce on parents' mental health. Moreover, it is important to treat parent–child contact as a dynamic process because prior studies have shown that estranged parent–child relationships are temporary in most cases (Agllias, 2013; Becker & Hank, 2021; Reczek et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the same logic, having no contact with one child may be sufficient to aggravate the impact of divorce on parents' mental health. Moreover, it is important to treat parent–child contact as a dynamic process because prior studies have shown that estranged parent–child relationships are temporary in most cases (Agllias, 2013; Becker & Hank, 2021; Reczek et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Higher‐order marriage, younger age, racial‐ethnic minority status, and lack of socioeconomic resources are positively associated with depressive symptoms among older adults (Lin et al, 2019). We also consider the number of adult children and the proportion of adult daughters because the larger the family size, the more likely it is that the respondents may have at least one child with whom they are disconnected or have frequent contact (Gilligan, Suitor, & Pillemer, 2015; Uhlenberg & Cooney, 1990; Ward et al, 2009) and daughters are less likely to become estranged from parents than are sons (Reczek et al, 2022).…”
Section: The Present Studymentioning
confidence: 99%